Development Of Prototype Remote Sensing Kit For Subcutaneous And Brain Glucose Monitoring [QD321. F237 2007 f rb]. - Ahmad, Farook (2007)

(untitled)
The study of subcutaneous and brain striatum glucose levels employing wireless glucose microsensor was proposed. A new implantable glucose sensor has been fabricated by immobilizing glucose oxidase on a chemically – modified carbon fiber prior to dipping in rat’s serum for 3 days for preconditioning.